Outcomes of use of electromagnetic guidance with responsive insertion technology (RIT) during colonoscopy: a prospective randomized controlled trial - Peter, Shajan; Reddy, Nipun B.; Naseemuddin, Mohammed; Zaibaq, Jenine N.; McGwin, Gerald; Wilcox, C. Mel (Endoscopy International Open, 2019)
Background and study aims Colonoscopy can be technically challenging and cause discomfort in patients. The integrated Scope Guide assist is built in to show that with its use outcomes are improved during colonoscopy. We aimed to test the usefulness of the Magnetic Scope Guide Assist (ScopeGuide) with respect to cecal intubation time, and other procedural quality outcomes.Patients and methods We conducted a prospective study of outpatients undergoing elective colonoscopy at the endoscopic units of the University of Alabama at Birmingham (UAB) from March 2016 to July 2016. Patients were randomly assigned in a 1:1 block design to groups that either had standard colonoscopy or Scope-guided colonoscopy. The primary outcome measure was cecal intubation time (CIT). Secondary outcome measures included use of manual pressure, position changes for cecal intubation and sedation requirements.Results Three hundred patients were randomized to either group; standard (n = 150) vs. Scope-guided (n = 150). The mean CIT was not statistically different for the standard and the Scope-guided groups (4.6 vs. 4.3 minutes; P = 0.46). There were also no statistical differences in frequency of manual pressure applied (16.7 % for Scope-guided vs. 19.1 % for standard; P = 0.65) or position changes (11.4 % for scope guided vs. 8.8 % standard; P = 0.56). Sedation requirements showed lesser use of midazolam (3.9 mg vs. 4.7 mg, P = 0.003) in the Scope-guide group, while there was no significant difference in use of fentanyl (fentanyl – 62.1 mg vs. 68.9 mg, P = 0.09 similar between groups, for Scope-guided vs. standard groups, respectively). Adverse events were similar in both groups.Conclusions In patients undergoing routine elective colonoscopy, use of ScopeGuide by experienced colonoscopists did not improve CIT or affect the frequency of ancillary maneuvers. The benefit of this device during training of endoscopists could be considered for further studies.